Mapping the evolving definitions of translational research. Issue 1 (2nd February 2017) - Fort, Daniel G.; Herr, Timothy M.; Shaw, Pamela L.; Gutzman, Karen E.; Starren, Justin B.
Abstract : Objective: Systematic review and analysis of definitions of translational research. Materials and methods: The final corpus was comprised of 33 papers, each read by at least 2 reviewers. Definitions were mapped to a common set of research processes for presentation and analysis. Influence of papers and definitions was further evaluated using citation analysis and agglomerative clustering. Results: All definitions were mapped to common research processes, revealing most common labels for each process. Agglomerative clustering revealed 3 broad families of definitions. Citation analysis showed that the originating paper of each family has been cited 10 times more than any other member. Discussion: Although there is little agreement between definitions, we were able to identify an emerging consensus 5-phase (T0–T4) definition for translational research. T1 involves processes that bring ideas from basic research through early testing in humans. T2 involves the establishment of effectiveness in humans and clinical guidelines. T3 primarily focuses on implementation and dissemination research while T4 focuses on outcomes and effectiveness in populations. T0 involves research such as genome-wide association studies which wrap back around to basic research. Conclusion: We used systematic review and analysis to identify emerging consensus between definitions of translational research phases.